Anti-inflammatory, Analgesic and Antiulcer properties of Porphyra vietnamensis - Saurabh Bhatia; Kiran Sharma; Ajay Sharma; Kalpana Nagpal; Tanmoy Bers (Mashhad University of Medical Sciences, 2014)
Objectives: Aim of the present work was to investigate the anti-inflammatory, analgesic and antiulcer effects of red seaweed Porphyra vietnamensis (P. vietnamenis). Materials and Methods: Aqueous (POR) and alcoholic (PE) fractions were successfully isolated from P. vietnamenis. Further biological investigations were performed using a classic test of paw edema induced by carrageenan, writhing induced by acetic acid, hot plate method and naproxen induced gastro-duodenal ulcer. Results: Among the fractions POR showed better activity.  POR and PE significantly (p < 0.05) reduced carrageenan induced paw edema in a dose dependent manner. In the writhing test POR significantly (p < 0.05) reduced abdominal writhes than PE.  In hot plate method POR showed better analgesic activity than PE. POR showed comparable ulcers reducing potential (p